Aging brain: exploring the interplay between bone marrow aging, immunosenescence, and neuroinflammation - Müller, Ludmila; Di Benedetto, Svetlana (Frontiers in Immunology, 2024)
Aging is a complex process characterized by a myriad of physiological changes, including alterations in the immune system termed immunosenescence. It exerts profound effects on both the bone marrow and the central nervous system, with significant implications for immunosenescence in neurological contexts. Our mini-review explores the complex relationship between bone marrow aging and its impact on immunosenescence, specifically within the context of neurological diseases. The bone marrow serves as a crucial hub for hematopoiesis and immune cell production, yet with age, it undergoes significant alterations, including alterations in hematopoietic stem cell function, niche composition, and inflammatory signaling. These age-related shifts in the bone marrow microenvironment contribute to dysregulation of immune cell homeostasis and function, impacting neuroinflammatory processes and neuronal health. In our review, we aim to explore the complex cellular and molecular mechanisms that link bone marrow aging to immunosenescence, inflammaging, and neuroinflammation, with a specific focus on their relevance to the pathophysiology of age-related neurological disorders. By exploring this interplay, we strive to provide a comprehensive understanding of how bone marrow aging impacts immune function and contributes to the progression of neurological diseases in aging individuals. Ultimately, this knowledge can hold substantial promise for the development of innovative therapeutic interventions aimed at preserving immune function and mitigating the progression of neurological disorders in the elderly population.